Statin Drug Therapy May Increase COVID-19 Infection - Shrestha, Sanjaya Kumar (Nepalese Medical Journal, 2020)
Enveloped viruses like Coronavirus acquire their envelope from the host cell membrane which is a bilayer of phospholipid interspersed with cholesterol molecules and proteins. Viruses enter their host cell by coming in contact with their specific receptors. Experiments have shown that when cell membranes are depleted of cholesterol in vitro by Methyl beta cyclodextrin (MβCD) these Coronaviruses are not able to enter the host cell membrane by the process of receptor mediated endocytosis. Statin inhibits HMG Co-A reductase, a key enzyme in the Mevalonate pathway resulting into either very low or no production of endogenous cholesterol by the human cells. This results into upregulation of LDL-R in the cell membrane which may lead to more cholesterol getting incorporated into the cell membrane through LDL-C from the plasma creating greater number of lipid rafts suitable for entry of enveloped viruses by receptor-mediated endocytosis.